Nature Bible puppet mania - Whiting, Karen H. (Monterey, CA : Healthy Learning, 2016)
Karen, an accomplished puppeteer and leader of youth puppet ministry teams, shares construction ideas, technique and character voice advice, and Bible story skits for a wide variety of animal puppet characters.
The world of puppetry -- Every puppet needs a helping hand -- Folding up puppets -- Moveable mouth finger puppets -- Boxed-in puppets -- Scrappy puppets -- Baggy puppets and puppet voices -- Plated puppets with special character traits -- Props with pizzazz -- Puppet skits and performances -- Creating puppet scripts -- Benefits of using puppets.
Keywords: Puppet theater in Christian education; Puppets; Puppet making; Puppet plays; Bible plays; Church work with children